2018
DOI: 10.3389/fpsyt.2018.00565
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Psychosocial Barriers and Facilitators to Smoking Cessation in People Living With Schizophrenia

Abstract: Background: People living with schizophrenia are less likely to quit smoking compared with the general population and people living with other psychiatric disorders. Understanding the schizophrenia-specific psychosocial barriers and facilitators to smoking cessation is important for designing effective smoking cessation interventions. We aimed to systematically review research examining psychosocial barriers and facilitators to smoking cessation in people living with schizophrenia.Methods: We followed the PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 71 publications
4
42
2
Order By: Relevance
“…Similar to other studies of adults with serious mental illness, in general [ 10 , 12 , 13 , 33 ], and young people with mental health conditions, in particular [ 47 ], participants described their main barriers to quitting as inability to resist cravings, using smoking to manage mental health symptoms, and smoking out of habit. Yet, only a few suggested that apps could teach strategies to overcome these barriers.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Similar to other studies of adults with serious mental illness, in general [ 10 , 12 , 13 , 33 ], and young people with mental health conditions, in particular [ 47 ], participants described their main barriers to quitting as inability to resist cravings, using smoking to manage mental health symptoms, and smoking out of habit. Yet, only a few suggested that apps could teach strategies to overcome these barriers.…”
Section: Discussionmentioning
confidence: 59%
“…A significant body of literature [ 9 - 12 ] has described unique challenges faced by people with serious mental illness who wish to quit smoking, which include both sociocultural influences (such as lower education and income, as well as higher stress levels) and neurobiological influences (including the modulating effect of nicotine on dopaminergic pathways in schizophrenia). Additionally, people with serious mental illness may endorse using tobacco to manage challenging psychiatric symptoms and to overcome difficulties with socialization [ 10 , 12 , 13 ]. Furthermore, some cessation medications (eg, bupropion) may not be indicated for a subset of people with serious mental illness [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation (including alienation, stigma and loneliness) is commonly reported by people with SMI (35) and is a barrier to quitting smoking (36, 37). Evidence suggests that smoking behaviour is influenced by social networks and that groups of people quit together via social contagion (38).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are often less likely to be formally supported in their efforts to stop smoking and are also less likely to be able to afford nicotine replacement products. Ongoing stigma, discrimination, inequality, and social exclusion are also considered to play a part in both why people smoke and add to the challenges of quitting (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, supporting people to quit smoking is an important strategy to deal with this significant and potentially increasing mortality gap, especially where cessation treatments also encourage the adoption of a healthy lifestyle that may concurrently address other physical health risk factors that people living with schizophrenia commonly experience. Lum et al (8) found that for people living with schizophrenia, health concerns are the highest reason to quit, and in some cases, the perceived smoking related health implications are the most negative consequence of smoking.…”
Section: Introductionmentioning
confidence: 99%